Boundary-value problems with parameters for a multifrequency oscillation system - Petryshyn, Ya. R.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
By using the averaging method, we prove the solvability of boundary-value problems with parameters for nonlinear oscillation systems. We obtain estimates for the deviation of solutions of averaged problems from solutions of original problems.